Stock market wizards : interviews with America's top stock traders - Schwager, Jack D. (New York : HarperBusiness, 2003)
This book features interviews with a variety of traders who achieved financial success during the glory days of the Internet boom. It discussed traders from a broad financial spectrum - stocks, bonds, currencies and futures. It focuses on traders in the stock market.
Includes bibliographical references and index.
lje 13/07/06
Keywords: Stockbrokers; Investment advisors; Floor traders (Finance); Futures market; Financial futures